Pharmacophylogenetic study of Scutellaria baicalensis and its substitute medicinal species based on the chloroplast genomics, metabolomics, and active ingredient - Shen, Jie; Li, Pei; Wang, Yue; Yang, Kailing; Li, Yue; Yao, Hui; Wang, Qiang; Xiao, Peigen; He, Chunnian (Frontiers in Plant Science, 2022)
The genetic relationships among Scutellaria species remain unclear because of the large number of species and complex trait variation. The usage of S. baicalensis and its four substitute medicinal species (S. amoena, S. hypericifolia, S. likiangensis, and S. viscidula) in traditional medicines makes their specialized metabolism important in China, but interspecific genetic and chemical differences have rarely been reported for these species. In this study, the chloroplast genomes of four substitute species for S. baicalensis were assembled, and comparative and phylogenetic analyses were performed with these species and other Scutellaria relatives. In addition, metabolomics analyses were performed and the contents of the main active compounds were determined to reveal the interspecific chemical diversity of S. baicalensis and its four substitute species. The full lengths of their chloroplast genomes ranged from 151,574-151,816 bp with an average GC content of 38.34%, and a total of 113 genes were annotated. In the chloroplast genomes of S. baicalensis and its four substitutes, one hypervariable region (petA-psbL) is proposed as a potential DNA barcode. Phylogenetic analysis showed that the subdivision of the genus Scutellaria should be reconsidered. The metabolomics and content determination analyses showed that the four species exhibit metabolism similar to that of S. baicalensis in different parts. Except for the roots of S. likiangensis, all parts of the substitute species showed high contents of baicalin. Genetic and chemical analyses of four substitute medicinal species for S. baicalensis were performed here for the first time, and their pharmacophylogenetic relationships were further explored, providing a scientific basis for the subsequent development of the medicinal value and resource utilization of Scutellaria.